2006
DOI: 10.1002/qua.21220
|View full text |Cite
|
Sign up to set email alerts
|

L2 discretization of Sturmian wave functions for Coulomb‐like potentials

Abstract: ABSTRACT:In this work we introduce a method to construct Sturmian functions for general interaction potentials in two-body problems. We expand these Sturmians on a finite L 2 space, using N Laguerre basis functions to obtain a discrete set of eigenvalues for positive and negative energies. Orthogonality and closure relations are thus rewritten for these expansions; completeness is achieved through increasing the basis size. We apply the method to the Coulomb and Herman and Skillman potential. We study the beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 31 publications
0
28
0
Order By: Relevance
“…It has been shown that the coefficients (9) are polynomials in β ν , and these eigenvalues are the N solutions of [12] …”
Section: A Quadrature Schemementioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that the coefficients (9) are polynomials in β ν , and these eigenvalues are the N solutions of [12] …”
Section: A Quadrature Schemementioning
confidence: 99%
“…We first discuss the general theory in Section 2.1. In Section 2.2 and 2.3 we review the quadrature and finite differences scheme used to obtain a discrete charge spectrum for any (negative or positive) energy [12]. The extension to the problem of two-electron atoms is discussed in Section 3.…”
Section: Introductionmentioning
confidence: 99%
“…The three-body solutions that are obtained with them are equivalent, although the basis functions they produce differ considerably. In the three-body context, the SW basis was used in [23], and both types were used in [24], where they were generated with two different methodologies [15,20].…”
Section: B Basis Set Typesmentioning
confidence: 99%
“…where H TP is the matrix representation of the operators in (15), separating the overlapping term, whose elements are O | n a ,n b . Similarly, the F vector is the projection of the RHS of Eq.…”
Section: Fast Electron Regime Modelmentioning
confidence: 99%
See 1 more Smart Citation